2007
DOI: 10.1021/bm700854j
|View full text |Cite
|
Sign up to set email alerts
|

Shell Cross-Linked Hyaluronic Acid/Polylysine Layer-by-Layer Polyelectrolyte Microcapsules Prepared by Removal of Reducible Hyaluronic Acid Microgel Cores

Abstract: Shell cross-linked hollow polyelectrolyte microcapsules composed of hyaluronic acid (HA) and poly- l-lysine (PLL) were prepared by layer-by-layer (LBL) adsorption and subsequent core removal by a reductive agent. Disulfide cross-linked HA microgels were used as template core materials for the LBL deposition on the surface and removed by treatment of dithiothreitol at neutral pH condition. HA/PLL polyelectrolyte multilayers on the shell were chemically cross-linked via carbodiimide chemistry, and their physicoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 40 publications
1
62
0
1
Order By: Relevance
“…As interactions between the polyelectrolytes are usually weaker in the case of polysaccharides, there is now a search for milder conditions for core dissolution in aqueous conditions, and in particular for lowering the osmotic pressure that is produced during core dissolution. To this end, biodegradable cores such as CaCO 3 are preferred [62,63], as well as other kinds of template such as microgels [64]. LbL assemblies based on HA have only recently been the basis for microcapsule formation from a CaCO 3 template [62].…”
Section: Microcapsules and Membranes Based On Polysaccharide Multilaymentioning
confidence: 99%
See 1 more Smart Citation
“…As interactions between the polyelectrolytes are usually weaker in the case of polysaccharides, there is now a search for milder conditions for core dissolution in aqueous conditions, and in particular for lowering the osmotic pressure that is produced during core dissolution. To this end, biodegradable cores such as CaCO 3 are preferred [62,63], as well as other kinds of template such as microgels [64]. LbL assemblies based on HA have only recently been the basis for microcapsule formation from a CaCO 3 template [62].…”
Section: Microcapsules and Membranes Based On Polysaccharide Multilaymentioning
confidence: 99%
“…The conditions for core dissolution were carefully investigated and it was found that EDTA or citric acid are successful chelating agents. However, in some cases, chemical crosslinking prior to core degradation is necessary [62,64] in order to strengthen the PEM film.…”
Section: Microcapsules and Membranes Based On Polysaccharide Multilaymentioning
confidence: 99%
“…[96] Similar findings were reported later by different research groups, who used hyaluronidase and chitinase to decompose capsules containing hyaluronic acid or chitosan, respectively, as membrane components. [97][98][99]102] The transition from an oxidative to a reductive environment has also been exploited to trigger the decomposition of PMLCs following cellular uptake. As mentioned in Section 2.3, disulfide bonds can act as bioresponsive cross-links that are cleaved to single thiols upon reduction.…”
Section: Stimuli-responsive Releasementioning
confidence: 99%
“…[28,29] Possessing the properties of micelles, microgels, nanoparticles, and dendrimers, SCL micelles with stimuliresponsive coronas are preferred in practical applications, such as targeted drug delivery, tunable release, recyclable catalysts, emulsification, sequestration of metabolites and entrapment of environmental pollutants. [17][18][19][28][29][30][31][32][33] Another focus of interest has been tunable hydrophilic cores, which do not require any core removal and may lead to the release of encapsulated actives triggered by different chemical stimuli such as pH, temperature and ionic strength. [14,34] Manipulating solution pH is often preferred over manipulating temperature or salt concentration.…”
Section: Introductionmentioning
confidence: 99%